Application of Spiritual Emotional Freedom Technique on Anxiety of Hypertension Patients in the Work Area of the Simpang Periuk Public Health Center Lubuklinggau City - Nurna Ningsih; Lukman; Cindy Ardianty (PT FORMOSA CENDEKIA GLOBAL, 2022)
Hypertension can be caused by various factors, including individual anxiety and stress, and hypertension can trigger anxiety in sufferers. Efforts that can be made to prevent and overcome hypertensive anxiety can be achieved by treatment or non-pharmacological interventions spiritual emotional freedom technique (SEFT), which can maintain blood pressure stability in the normal range. Various SEFT studies have shown a decrease in anxiety levels. The purpose of the study: to obtain an overview of nursing care in the application of spiritual emotional freedom technique in reducing anxiety in hypertensive patients. Research method: using descriptive research with a case study approach. Performed on both subjects with a medical diagnosis of hypertension and complaints of mild to moderate anxiety. Activities are carried out 2x/week with a duration of 20-30 minutes. The results: there was a decrease in the anxiety of both respondents from moderate to mild anxiety, with complaints of reduced weakness, no cold sweats, relaxed body, and no heart palpitations. Simpang Periuk, Lubuklinggau City.